Maternal Affective Expression and Adolescents' Subjective Experience of Positive Affect in Natural Settings. (23rd October 2017) - Griffith, Julianne M.; Silk, Jennifer S.; Oppenheimer, Caroline W.; Morgan, Judith K.; Ladouceur, Cecile D.; Forbes, Erika E.; Dahl, Ronald E.
Abstract : This study investigated the association between maternal affective expression during laboratory‐based interaction tasks and adolescents' experience of positive affect (PA) in natural settings. Participants were 80 healthy adolescents and their mothers. Durations of maternal positive (PA) and negative affective (NA) expressions were observed during a conflict resolution task and a positive event planning interaction task. Ecological momentary assessment (EMA) procedures were employed to assess adolescents' momentary and peak experience of PA in daily life. Results indicated that maternal NA, but not maternal PA, was related to adolescents' EMA‐reported PA. Adolescents whose mothers expressed more NA experienced less PA in daily environments. Results suggest that adolescents' exposure to maternal negative affective behavior is associated with adolescents' subjective daily well‐being.